The comparison of children customary clothes between the royal and communal society in Malay circumcise ceremony / Nor Idayu Ibrahim, Arba’iyah Ab. Aziz and Mohamad Kamal Abd. Aziz - Ibrahim, Nor Idayu; Ab. Aziz, Arba’iyah; Abd. Aziz, Mohamad Kamal (Universiti Teknologi MARA, 2019)
Islam emphasizes the value of cleanliness starting from their childhood ages. The Malay traditions that usually followed by a custom ceremony which is called Adat Berkhatan for boys or male gender. This tradition has been inherited since their ancestor’s times as it is a symbolic period into a new childhood phase before entering a maturity phase. This study aims to identify the children's customary attire in two types of Malay social groups namely the royalties and the communal society during the circumcise ceremony besides documenting the knowledge of the customary clothes. Meyer Schapiro's theory of style is used in this research. The theory is equivalent to feature the Malay children's customary clothes’ style worn during the circumcise ceremony. Methods applied was the qualitative method due to its flexibility in approaching the informants to have precise data and reliable facts including their photos collection of the ceremony had been analyzed. To conclude, this research hopefully will benefit and provide an essential source of references to the Malay culture including researchers, academicians, scholars, students, cultural activists, and the whole Malay communities throughout the region.